Reconfiguring Mosque-Based Civic Networks: Religious Messaging, Emotional Appeal, and Social Intimacy in Hijrah Movement of ‘Kopdar Masjid BDG Raya’ WhatsApp Group - Abdurrahman, Muhammad Sufyan; Syifaa Sutarjo, Moch. Armien; Rohimakumulloh, Muhammad Al Assad; Salma, Aqida Nuril (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2025)
This study examines how the WhatsApp group Kopdar Masjid BDG Raya operates as a civic micro-network that reshapes mosque-based Islamic participation among urban youth engaged in the hijrah movement in Greater Bandung. Using virtual ethnography and one-year observation (July 2023–June 2024), the research explores how religious messaging, emotional resonance, and social intimacy are constructed and maintained in everyday group interaction. The findings show that daily spiritual prompts, repentance narratives, and offline gatherings foster a collective moral journey rooted in transformation and belonging. Rather than solely distributing da‘wa content, the group nurtures trust, accountability, and coordinated mosque-based activities that deepen civic religiosity. While the group demonstrates stability and active participation, it is not without limitations. Informants noted some content fatigue and silent readership patterns, as well as subtle frictions when mosque administrators differed in da‘wa orientation or program intensity. These limitations suggest that digital hijrah activism relies on negotiated interaction, ongoing trust-building, and careful coordination with offline mosque authorities. This paper contributes to the study of digital Islamic movements by highlighting the evolving role of WhatsApp as a medium for sustaining spiritual commitment, facilitating civic bonds, and navigating the informal structures of religious authority in contemporary Indonesian cities.